A catalase-powered self-oxygen-generating soft nanomotor for photodynamic therapy of osteosarcoma - Xinyi Tan; Yu Wang; Ying Yuan; Yuchen Song; Jianghan Xia; Xinzeyu Yi; Zheng Wang; Huiyun Gu; Pengcheng Li; Zhaogang Teng; Aixi Yu (Materials Today Bio)
Over the past few decades, the development of novel osteosarcoma treatments has been confronted with the challenges of inadequate drug accumulation within tumors and hypoxic tumor microenvironments. The active propulsion advantage of micro/nano-motors (MNMs) has been harnessed to enhance the delivery efficiency of photosensitizers and improve tumor penetration. Given that soft nanoparticles can enhance blood circulation, cellular uptake and tumor accumulation/penetration, we composite soft mesoporous organosilica and catalase to construct self-oxygen-generating soft nanomotors as a drug delivery platform of Ce6, namely SMONs-CAT-Ce6 (SCC) and investigated the uptake and therapeutic efficiency of it in osteosarcoma both in vitro and in vivo. The results demonstrate the ability of soft nanomotors to enhance the internalization of photosensitizers by tumor cells and increase the accumulation and penetration of Ce6 in tumors. Moreover, catalase-derived oxygen effectively alleviates the hypoxic microenvironment in solid tumors, resulting in an enhanced inhibitory effect on tumor growth and improved prevention of lung metastasis in 143B osteosarcoma-bearing mice through SCC-based photodynamic therapy. The present study provides objective evidence that supports the potential of self-oxygen-generating soft nanomotors as an efficient photodynamic drug delivery system with tumor-penetrating capabilities and a high uptake device for osteosarcoma treatments.